2016
DOI: 10.5424/sjar/2016141-8752
|View full text |Cite
|
Sign up to set email alerts
|

Emergence dynamics of barnyardgrass and jimsonweed from two depths when switching from conventional to reduced and no-till conditions

Abstract: <p>A cylinder experiment was conducted in northern Greece during 2005 and 2006 to assess emergence dynamics of barnyardgrass (<em>Echinochloa crus-galli</em> (L.) Beauv.) and jimsonweed (<em>Datura stramonium </em>L.) in the case of a switch from conventional to conservation tillage systems (CT). Emergence was surveyed from two burial depths (5 and 10 cm) and with simulation of reduced tillage (<em>i.e.</em> by soil disturbance) and no-till conditions. Barnyardgrass em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…The cessation of emergence with the closing of the leaf canopy has already been documented [5] and explained by the change in soil climate. However, studies based on determination of emergence pattern often are performed in a crop-free field [36][37][38]. Nevertheless, when E. crus-galli emergence was observed without the crop at 12 sites in the United States, the emergence extended into September [39]-much longer than in our study.…”
Section: Field Experimentscontrasting
confidence: 65%
See 1 more Smart Citation
“…The cessation of emergence with the closing of the leaf canopy has already been documented [5] and explained by the change in soil climate. However, studies based on determination of emergence pattern often are performed in a crop-free field [36][37][38]. Nevertheless, when E. crus-galli emergence was observed without the crop at 12 sites in the United States, the emergence extended into September [39]-much longer than in our study.…”
Section: Field Experimentscontrasting
confidence: 65%
“…The effect of tillage on the vertical distribution of seed in the seed bank is well known, and different tillage practices can significantly affect field emergence. However, Vasileiadis et al [37] concluded that the emergence of E. crus-galli was stable over the years under different simulated tillage systems (conventional, reduced, and, no-till), so AlertInf could be adopted for maize grown under different tillage conditions considering this fact. Another factor that could influence the emergence and effectiveness of the model is soil type, which was not considered in this experiment and should be further investigated.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Nevertheless, its presence was the highest in CT and MT. Some authors [21] also found that emergence of E. crus-galli was stable in treatments with different tillage depths during their research. According to Chauhan and Johnson [22], this weed can become a serious problem in NT.…”
Section: Discussionmentioning
confidence: 85%